Komunikacja interpersonalna realizowana za pośrednictwem komunikatorów internetowych jako źródło ryzyka w zarządzaniu projektami informatycznymi - Winiarski, Jacek (Interpersonal communication via instant messengers as a source of potential risk in Information technology projects management, 2006)
This work describes changes resulting form the use of internet communicators by companies involved in computer technology projects. The author analyses the main barriers in interpersonal communication which may occur at computer technology business. Also available internet tools for interpersonal communication are evaluated. The paper attempts to show how the use of the internet communicators for information interchange may modify typical communication barriers among employees working on information technology project.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 272-280